2014
DOI: 10.1111/jop.12150
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effect of Mentha piperita on dimethylbenz[a]anthracene and formaldehyde‐induced tongue carcinogenesis in mice (histological and immunohistochemical study)

Abstract: Our study demonstrated that Mentha piperita has inhibited the initiation and promotion of oral dysplastic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Besides, the scientific studies of plants used in ethnic practice have led to the discovery of many valuable drugs [23,24]. The Lamiaceae or Labiatae consists of 210 genera, 3500 species and widely used culinary herbs, such as rosemary, sage, oregano, peppermint and many others from which several herbal products have shown potential anticarcinogenic properties [25,26]. Plectranthus amboinicus is an edible, nontoxic, well-known plant belongs to family Lamiaceae, it contains flavonoids, rosmarinic acid, phenolic compounds and has been demonstrated for the treatment of various diseases [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the scientific studies of plants used in ethnic practice have led to the discovery of many valuable drugs [23,24]. The Lamiaceae or Labiatae consists of 210 genera, 3500 species and widely used culinary herbs, such as rosemary, sage, oregano, peppermint and many others from which several herbal products have shown potential anticarcinogenic properties [25,26]. Plectranthus amboinicus is an edible, nontoxic, well-known plant belongs to family Lamiaceae, it contains flavonoids, rosmarinic acid, phenolic compounds and has been demonstrated for the treatment of various diseases [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…For the first time observed that the chloroform/ mint extract protected against the γ-radiationinduced oxidative stress and mortality [7,16]. Also, was shown that the M. piperita extract possesses significant radioprotective properties [16,17] in patients undergoing cancer treatment [7], and for reduction in irritable bowel syndrome (IBS) symptoms [18,19] and anticancer properties [20].…”
Section: Introductionmentioning
confidence: 99%
“…The plant are commonly used in folk medicine for carminative, antispasmodic, antiemetic, diaphoretic, analgesic, anti-inflammatory, stimulant, emmenagogue and anticatharrhal applications. Its essential oils are generally used externally for antipruritic, astringent, rubefacient, antiseptic and antimicrobial purposes, and for treating neuralgia, myalgia, headaches and migraines [19][20][21][22][23][24][25][26][27][28] . In addition, gamma-irradiation is the process of exposing products to radiation to delay ripening, inhibit sprouting and extend shelf-life by reducing spoilage organisms, helping to meet quarantine standards for export to foreign markets 29 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gamma-irradiation is the process of exposing products to radiation to delay ripening, inhibit sprouting and extend shelf-life by reducing spoilage organisms, helping to meet quarantine standards for export to foreign markets 29 . The gamma irradiation method is allowed for the decontamination of dried herbs, spices and vegetable seasonings with a maximum overall average absorbed dose of 10 kGy but this limitation has been raised by the Food and Drug Administration (FDA) to doses of 30 kGy for these products 25,26 . One of the most problems using gamma irradiation is the adverse effects on the biological activities of the medicinal plants [30][31] .…”
Section: Introductionmentioning
confidence: 99%